Advances in cryptology - ASIACRYPT 2015 : 21st International Conference on the Theory and Application of Cryptology and Information Security, Auckland, New Zealand, November 29-December 3, 2015, proceedings, parts 1 & 2 /: 21st International Conference on the Theory and Application of Cryptology and Information Security, Auckland, New Zealand, November 29-December 3, 2015, proceedings, parts 1 & 2. (2015) - Unknown
No abstract available